Experimental Study of Hydrogasification of Lignite and Subbituminous Coal Chars - Stanisław Gil; Adam Smoliński (The Scientific World Journal)
The experimental facility for pressure hydrogasification research was adapted to the pressure of 10 MPa and temperature of 1300 K, which ensured repeatability of results and hydrogen heating to the process temperature. A hydrogasification reaction of chars produced from two rank coals was investigated at temperatures up to 1173 K, pressures up to 8 MPa, and the gas flow rates of 0.5–5 dmn3/min. Reactivity of the “Szczerców” lignite char was found to be slightly higher than that of the subbituminous “Janina” coal char produced under the same conditions. A high value of the char reactivity was observed to a certain carbon conversion degree, above which a sharp drop took place. It was shown that, to achieve proper carbon conversion, the hydrogasification reaction must proceed at a temperature above 1200 K.